Effectiveness of Methenamine for UTI Prevention in Older Adults. Issue 4 (April 2020) - Snellings, Marina S.; Linnebur, Sunny A.; Pearson, Scott M.; Wallace, Jeff I.; Saseen, Joseph J.; Fixen, Danielle R.
Background: Methenamine is a drug used for the prevention of lower urinary tract infections (UTIs). However, efficacy has not been established in older adults or patients with varying degrees of kidney function.Objective: To evaluate the effectiveness of methenamine for the prevention of UTI in adults 60 years and older.Methods: This was a retrospective, pre-post, observational study. The study included primary care patients 60 years and older who were taking methenamine between January 1, 2015, and September 30, 2018. The primary outcome was the time to first UTI after methenamine initiation compared with the average time between UTIs in the 12 months prior to methenamine initiation.Results: Of 434 patients reviewed, 150 met inclusion criteria. The average time to UTI was 3.3 months prior to methenamine initiation compared with 5.5 months after methenamine initiation ( P = 0.0004). There were 33 patients (22%) who did not have a UTI after methenamine initiation. Also, 14 patients (9.3%) had a calculated CrCl <30 mL/min at baseline. The average time to UTI in these patients was 3.3 months prior to methenamine initiation compared with 12.7 months after initiation ( P < 0.0001).Conclusion and Relevance: Methenamine use was associated with a longer time to UTI in older adults with varying degrees of kidney function. The effectiveness of methenamine appeared to be similar regardless of kidney function, which is new evidence. Because of a lack of acquired resistance, methenamine may be an effective option for UTI prophylaxis in older adults.